The GID ubiquitin ligase complex is a regulator of AMPK activity and organismal lifespan. Issue 9 (1st September 2020) - Liu, Huaize; Ding, Jie; Köhnlein, Karl; Urban, Nadine; Ori, Alessandro; Villavicencio-Lorini, Pablo; Walentek, Peter; Klotz, Lars-Oliver; Hollemann, Thomas; Pfirrmann, Thorsten
ABSTRACT: The AMP-activated protein kinase (AMPK) regulates cellular energy homeostasis by sensing the metabolic status of the cell. AMPK is regulated by phosphorylation and dephosphorylation as a result of changing AMP/ATP levels and by removal of inhibitory ubiquitin residues by USP10. In this context, we identified the GID-complex, an evolutionarily conserved ubiquitin-ligase-complex (E3), as a negative regulator of AMPK activity. Our data show that the GID-complex targets AMPK for ubiquitination thereby altering its activity. Cells depleted of GID-subunits mimic a state of starvation as shown by increased AMPK activity and macroautophagic/autophagic flux as well as reduced MTOR activation. Consistently, gid -genes knockdown in C. elegans results in increased organismal lifespan. This study may contribute to understand metabolic disorders such as type 2 diabetes mellitus and morbid obesity and implements alternative therapeutic approaches to alter AMPK activity. Abbreviations: ACTB: actin, beta; ADP: adenosine diphosphate; AMP: adenosine monophosphate; AMPK: AMP-activated protein kinase; ARMC8: armadillo repeat containing 8; ATP: adenosine triphosphate; BafA1: bafilomycin A1 ; BCAA: branched chain amino acid; BICC1: BicC family RNA binding protein 1; BSA: bovine serum albumin; CAMKK2 kinase: calcium/calmodulin dependent protein kinase kinase 2, beta; CHX: cycloheximide; DMEM: Dulbecco's modified Eagle's medium; E1: ubiquitin-activating enzyme; E2: ubiquitin-conjugating enzyme; E3: ubiquitin ligase; ECAR: extracellular acidification rate; FACS: fluorescent associated cell sorter; FBP1: fructose-bisphosphatase 1; FCCP: carbonyl cyanide-4 (trifluoromethoxy) phenylhydrazone; G6P: glucose-6-phosphate; GDP: guanosine diphosphate; GFP: green fluorescent protein; GID: glucose induced degradation deficient; GMP: guanosine monophosphate; GTP: guanosine triphosphate; HBP1: high mobility group box transcription factor 1; HPRT: hypoxanthine guanine phosphoribosyl transferase; KO: knock out; LE: long exposure; MAEA: macrophage erythroblast attacher; MAP1LC3B/LC3B: microtubule-associated protein 1 light chain 3 beta; MKLN1: muskelin 1; mRNA: messenger RNA; MTOR: mechanistic target of rapamycin; NES: normalized enrichment score; OCR: oxygen consumption rate; PBS: phosphate buffered saline; PCK1: phosphoenolpyruvate carboxykinase 1, cytosolic; PCR: polymerase chain reaction; PFA: paraformaldehyde; RANBP9: RAN binding protein 9; RING: really interesting new gene; RMND5: required for meiotic nuclear division5 homolog; RPS6: ribosomal protein S6; RPTOR: regulatory associated protein of MTOR, complex 1; SE: short exposure; SEM: standard error of the mean; SQSTM1/p62: sequestosome 1; TSC2: tuberous sclerosis complex 2; TUBA4A: tubulin; TUBE: tandem ubiquitin binding entities; Ub: ubiquitin; UPS: ubiquitin proteasome system; WDR26: WD repeat domain 26; WT: wild type.